Huanglongbing and Foliar Spray Programs Affect the Chemical Profile of “Valencia” Orange Peel Oil - Sun, Xiuxiu; Yang, Huqing; Zhao, Wei; Bourcier, Elise; Baldwin, Elizabeth A.; Plotto, Anne; Irey, Mike; Bai, Jinhe (Frontiers in Plant Science, 2021)
Florida orange trees have been affected by huanglongbing (HLB) for more than a decade. To alleviate disease-caused tree decline, maintain fruit productivity and reduce disease transmission, enhanced foliar spray programs combining vector control and nutritional supplementation have been applied to healthy and diseased trees. The aim of this research was to discover if the various foliar sprays affect fruit peel oil chemical components. In this study, ‘Valencia’ orange trees, with or without HLB (HLB+/-), were treated with the grower standard program (control, C) or one of four proprietary enhanced foliar spray programs (N1, N2, N3 and N4) over 16 months. Compared to HLB-, HLB+ samples had lower concentrations of typical peel oil components, including valencene, octanal and decanal, and were abundant in oxidative/dehydrogenated terpenes, such as carvone and limonene oxide. However, limonene, the dominant component was not affected by any treatment. Control and three out of four enhanced foliar spray programs, N2, N3 and N4, had very little influence on the chemical profiles of both HLB- and HLB+ samples, while N1 treatment greatly altered the chemical profile of HLB+ samples, resulting in peel oil similar to HLB- samples.